2021
DOI: 10.1007/s11557-021-01668-x
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomy and phylogeny of Aphanomycopsis bacillariacearum, a holocarpic oomycete parasitoid of the freshwater diatom genus Pinnularia

Abstract: Investigations into simple holocarpic oomycetes are challenging, because of the obligate biotrophic nature of many lineages and the periodic presence in their hosts. Thus, despite recent efforts, still, the majority of species described remains to be investigated for their phylogenetic relationships. One of these species is Aphanomycopsis bacillariacearum, the type species of the genus Aphanomycopsis. Species of Aphanomycopsis are endobiotic holocarpic parasites of diverse hosts (e.g., diatoms, desmids, dinofl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…It is noteworthy that phylogenetic investigations on diatom-infecting oomycetes have revealed that, contrary to the assumption of Dick (2001), these were not forming a monophyletic assemblage, but found to be spread throughout the phylogeny of oomycetes (Thines et al 2015;Buaya and Thines 2020b;Buaya et al 2017Buaya et al , 2021. The genus Ectrogella was revealed to indeed belong to the Saprolegniomycetes (Buaya and Thines 2019), which was also the case for Aphanomycopsis (Buaya et al 2021) and for Lagenisma (Thines et al 2015). In addition to this, it was also found that some diatom parasitoids formed a distinct, early-diverging lineage of oomycetes and were described as members of a new genus, Miracula (Buaya et al 2017).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…It is noteworthy that phylogenetic investigations on diatom-infecting oomycetes have revealed that, contrary to the assumption of Dick (2001), these were not forming a monophyletic assemblage, but found to be spread throughout the phylogeny of oomycetes (Thines et al 2015;Buaya and Thines 2020b;Buaya et al 2017Buaya et al , 2021. The genus Ectrogella was revealed to indeed belong to the Saprolegniomycetes (Buaya and Thines 2019), which was also the case for Aphanomycopsis (Buaya et al 2021) and for Lagenisma (Thines et al 2015). In addition to this, it was also found that some diatom parasitoids formed a distinct, early-diverging lineage of oomycetes and were described as members of a new genus, Miracula (Buaya et al 2017).…”
Section: Introductionmentioning
confidence: 88%
“…However, recent phylogenetic investigations have shown that Olpidiopsis is an early diverging lineage restricted to oomycete hosts, leading to the transfer of species infecting red algae to the genus Pontisma (Buaya et al 2019a). It is noteworthy that phylogenetic investigations on diatom-infecting oomycetes have revealed that, contrary to the assumption of Dick (2001), these were not forming a monophyletic assemblage, but found to be spread throughout the phylogeny of oomycetes (Thines et al 2015;Buaya and Thines 2020b;Buaya et al 2017Buaya et al , 2021. The genus Ectrogella was revealed to indeed belong to the Saprolegniomycetes (Buaya and Thines 2019), which was also the case for Aphanomycopsis (Buaya et al 2021) and for Lagenisma (Thines et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Samples collected and preserved in 70% ethanol in the same manner were deposited in the herbarium collection of the Senckenberg Museum of Natural History (Herbarium Senckenbergianum, FR), Cryptogams Section, Frankfurt am Main (accessions: FR-0046131 for isolate 1, FR-0046132 for isolate 2, both isolated from the same raw sample). Morphological characterisation of the parasite was done as described earlier (Buaya et al 2021 ) using a compound light microscope (Imager2, Carl Zeiss Göttingen, Germany) with DIC, and photographs were taken using a Zeiss Axiocam MRc5 (Carl Zeiss, Göttingen, Germany). In addition, cellulose presence in the thallus wall of the diatom parasitoid was tested using zinc iodine chloride solution (Carl Roth GmbH, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Some PCR amplicons were cloned as previously described (Buaya et al 2020b ). The resulting sequences were edited and assembled using Geneious (version 5.6, Biomatters, Auckland, New Zealand), and the assembled consensus sequences were added to the dataset of Buaya et al ( 2020b ), supplemented with additional sequences from Buaya et al ( 2021 ). Subsequently, alignments were done using mafft version 7 as implemented on the mafft webserver (Katoh et al 2019 ), with the Q-INS-i algorithm and a gap opening penalty of 2.4 to account for the high conservation of the nrSSU.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation